Community-Based Intervention for Hearing Loss: Impact of Hearing Screening Programme in Ondo West Local Government Area - Ikong M.A; Akpalaba I.O.; Olarinoye O.T.; James. R. O (Archives of Current Research International, 2024)
Introduction: The spectrum of hearing loss as a public health condition has continued to increase globally both in its pathological as well as demographic status. Consequently, a vast majority of people especially in Nigeria and other low income countries suffer from one psychological, economic, social and cognitive disadvantage of hearing loss to another. Aim: The aim of this study was to investigate the impact of hearing screening programmes as a means of Community-based intervention for hearing loss. Methods: Subjects in the study are patients who submitted for a free hearing screening programme within the months of March and May 2022, organized by the department of Ear, Nose and Throat, University of Medical Sciences Teaching Hospital, Ondo State, Nigeria. The hearing screening was carried out by Otorhinolaryngologist, Audiologists and Speech Therapists using, Otoscope, Tuning Forks, HearWHO mobile app, a well-structured questionnaire etc. Results: Of 356 patients who were screened, 80 presented with hearing related disorders such as hearing loss, tinnitus, canal blockage, polyps, otitis media and otitis externa. Interventions were administered accordingly, on either free or subsidized scale to patients. It was deduced that the majority of these patients would not have presented for hearing screening if it was not a free Community-based programme. Conclusion: Community-based hearing screening programmes enhance early identification of hearing disorders and commencement of hearing healthcare interventions especially in low income countries.